Tinjauan Prespektif Behavioristik: Strategi Pembelajaran Pendidikan Islam dalam Meningkatkan Kedisiplinan Beribadah Siswa di SMK Negeri 2 Barru Sulawesi Selatan - Rahmiati; Rusman; Ambo Dalle; Hamsa; Usman; Muzakkir (TAUJIH: Jurnal Pendidikan Islam, 2024)
This research aims to analyze Islamic Religious Education (PAI) learning strategies based on behavioristic theory at SMK Negeri 2 Barru to improve students' prayer discipline. Using a descriptive qualitative approach, data was collected through observation, interviews and documentation. Research findings show that PAI learning strategies are implemented through an integrative approach that includes three main dimensions: intracurricular, co-curricular and extracurricular. Intracurricular strategies include lectures, discussions and worship practices aimed at strengthening students' understanding of religious values. Co-curricular activities are focused on holding congregational prayers which are directly monitored by teachers, while extra-curricular activities include recitation competitions, recitations and lecture training. The application of behavioristic theory in learning makes a significant contribution to the formation of the discipline of worship. The main principle used is positive reinforcement, where teachers give appreciation and appreciation to students who show consistency in worship. The stimulus provided by the school environment is able to create a positive response in the form of increasing religious discipline. Research results reveal that students who regularly receive positive reinforcement tend to be more motivated to develop religious habits. However, research also identifies a major challenge, namely the lack of consistent support from the family and community outside of school. Overall, this research makes an important contribution to the development of effective PAI learning strategies. The results offer a new perspective on the application of behavioristic theory in religious education, with practical implications for creating more innovative and meaningful learning approaches.